Morocco : Legal and Judicial Sector Assessment - World Bank (Washington, DC, 2013)
The overall legal framework in Morocco is not a priority area for reform. The law-making process, however, is weak, resulting in poorly drafted laws, and legal dissemination is inadequate. Legal education relies upon outdated curricula and is offered in competing languages, French and Arabic, the selection of which largely determines students' choices for future employment. The training of legal professionals is minimal and is poorly supervised. The general public has little access to legal information. Legal aid is embryonic and restricted to criminal matters. This assessment of the legal and judicial sector offers recommendations in the areas of case law dissemination, capacity building of the law-making institutions, development of a legal toolkit for judges, redesign of legal studies, training of legal professionals to improve quality, supervision of translators and experts, redirecting the activities of lawyers towards legal advice, expanding the notaries, redesigning court operations, expanding judicial participation on the High Council for the Judiciary and ensuring greater judicial independence, offering professionalized training to the judiciary, including language proficiency as a criteria for recruitment and promotion, obtaining judicial consent for judicial transfers, making public judicial resources, improving the transparency of the inspection process, drafting a code of legal ethics, training for non-judicial appointments, developing court management capacities, improving personnel management, acknowledgment of the profession of registrar, reviewing and enforcing the regulations concerning judicial experts, further decentralizing of the management of the judicial budgets and development of budget management capacity, improving court statistics, upgrading judicial infrastructure, court construction and renovation, overhauling the entire enforcement system, development of public information procedures, improving access of the public to legal information and advice, and enactment of the arbitration code.